2004
DOI: 10.1002/gcc.20066
|View full text |Cite
|
Sign up to set email alerts
|

Loss of chromosome arm 18q with tumor progression in head and neck squamous cancer

Abstract: Loss of 18q was analyzed in 21 sets of head and neck squamous cell carcinoma (HNSCC) cell lines derived from primary and secondary tumors in the same patients. Only 3 of the 21 cell line pairs had no loss of 18q. In the remaining 18 sets, loss of heterozygosity (LOH) affecting 18q was found in either the primary or the secondary lines or both. In every case but one, the same chromosome was affected in both the primary and secondary cell lines. In 8 sets, the 18q loss occurred in the primary tumor and remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 14 publications
2
35
0
1
Order By: Relevance
“…Region 18q21 is one of the well-known instable chromosome regions in oral carcinomas, at which genetic alterations such as LOH or microsatellite instability have been frequently reported, indicating that there may be unidentified tumor suppressor gene in this region (16,18,20,25). Previously, we found a high frequency of LOH (43.8%) at 18q21 in OSCCs.…”
Section: -------------------------------------------mentioning
confidence: 66%
See 1 more Smart Citation
“…Region 18q21 is one of the well-known instable chromosome regions in oral carcinomas, at which genetic alterations such as LOH or microsatellite instability have been frequently reported, indicating that there may be unidentified tumor suppressor gene in this region (16,18,20,25). Previously, we found a high frequency of LOH (43.8%) at 18q21 in OSCCs.…”
Section: -------------------------------------------mentioning
confidence: 66%
“…Both SERPINB5 and SERPINB13 genes are located on chromosome 18q, which is the location of the serpin gene cluster and other members of serpin family. Frequent genetic alterations have been observed in this chromosomal region in head and neck malignancies (15)(16)(17)(18)(19)(20). We previously reported that loss of heterozygosity (LOH) at 18q21 was observed in 43.8% of oral squamous cell carcinomas, and that this was significantly correlated with the clinicopathological features (21).…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous loss of 18q has been reported in several types of carcinomas, for example colon cancer, 33 pancreatic carcinoma, 34 and head and neck squamous cell carcinoma. 35 These losses, including the tumor suppressor genes SMAD4, DCC, and GALR1, are associated with tumor progression and unfavorable prognosis. 33,34,36 Of interest, all but one of our mucoepidermoid carcinomas with loss of 18q were high-grade tumors that developed metastases (five cases) and/or recurrences (three cases).…”
Section: Discussionmentioning
confidence: 99%
“…In oral carcinomas, expression of the tumor suppressors p53, p14 ARF , p16 INK4a , FHIT, and RSSF1 was frequently inactivated in the early stage of carcinogenesis (1). Allelic imbalance at chromosome locus 18q is associated with progression and poor patient survival of head and neck carcinomas (2,3), and genetic abnormalities at 18q21 are observed in carcinomas of the oral cavity (National Center for Biotechnology Information Entrez Cancer Chromosome Database 3 ) and others (4)(5)(6). Although one tumor suppressor gene, deleted in colorectal carcinoma (DCC), exists at 18q21.1, recent investigations suggest the presence of additional tumor suppressors at 18q21.31 (7,8).…”
Section: Introductionmentioning
confidence: 99%